Surface Effect on the Nanowire Forest Indentation - Yang, F. (Проблемы прочности, 2018)
The surface effect on the mechanical behavior of a nanowire forest indentation is theoretically studied. The use of a large-radius spherical indenter revealed a complex deformation pattern of the nanowire forest. The nanowire forest compression, buckling and postbuckling were analyzed. The effect of surface and packing density on the nanowire forest behavior with the indentation depth is discussed. The results show that the surface effect is of importance for in-depth hardness. The analysis is instrumental in measuring the mechanical properties of the nanowire forest and in designing nanowire-forest devices for various applications